The meaning and essential nature of a profession: a multi-perspective approach. (2nd January 2020) - Abadi, Hossein Ali; Ayentimi, Desmond Tutu; Coetzer, Alan
ABSTRACT: In the existing literature, there is a lack of consensus among scholars within different research disciplines on the meaning and particularly essential elements of a profession. Consensus would be beneficial to the ongoing debates relating to the notion of a 'profession', and related concepts such as 'professionalisation' and 'professionalism', within the new social systems and organisational work context. To address this limitation of the literature, this paper aims to develop and propose a multidisciplinary understanding of the meaning and essential elements of a profession. To accomplish this aim, we draw on the disciplines of psychology, management and sociology and integrate these diverse perspectives to extend prior theorisations. Implications of our integrative analyses for advancing profession-related research and practice are discussed.